Advanced air quality monitoring: PM and ozone with Raspberry Pi and Arduino - M. Chandrakala; M. V. Lakshmaiah; P. Thimmaiah (Discover Applied Sciences)
Abstract Background There is a rising issue of pollution in the atmosphere. Particulate matter, CO, CO2, NO, NO2, ozone etc. are causing adverse impacts to the surrounding and the well-being of every individual living across the entire globe. Therefore, there is a stringent need to be aware of these atmospheric pollutants for safeguarding the quality of air that we human being breathe in. Materials In this work, we integrate microcontrollers like Arduino Uno and Raspberry Pi along with the primary measuring sensors like ozone sensor and PM7003 sensor for carrying out characterization of air quality and variability investigation of several traits/parameters by including but not limited to temperature, pressure, humidity, PM1, PM2.5, PM10, and ozone. By deploying Arduino Uno, Raspberry Pi and other miscellaneous components, we developed an interactive and effective method for collecting practical data corresponding to the quality of air. Results and discussion First, we present our experimental set-up along with its observations made using the set-up for the several parameters considered for measuring the air quality. Then, we present the graphical comparative study of traits/parameters like temperature, pressure, humidity, PM1, PM2.5, PM10, and ozone. Then, we present the summary of observations made for the major pollutants for characterization of air quality and variability investigation. Then, we carry out the case study using three different types of sensors like temperature, MQ2, and MQ4 sensors as an extension of the major segment of our work. Finally, the performance validation of measurement was done using four common performance indicators.